2012
DOI: 10.1055/s-0032-1316737
|View full text |Cite
|
Sign up to set email alerts
|

Some Practical Methods for the Application of 5-Metallo-1-benzyl-1H-tetrazoles in Synthesis

Abstract: Nucleophilic reagents such as 5-lithiotetrazoles are synthetically powerful tools for the installation of tetrazole functional groups, but they are of limited utility due to the instability of tetrazole-derived carbanions. Herein, we report practical methods for the generation and use of new 5-metallo-1-benzyl-1H-tetrazoles (M = K, MgX, ZnX) derived from either 1-benzyl-1H-tetrazole or 1-benzyl-5-bromo-1H-tetrazole. By varying the metal counterion, the tetrazole carbanion stability was improved. Potassium-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 3 publications
0
17
0
1
Order By: Relevance
“…The Wiedemann group reported some practical methods for the application of 5-metallo-1benzyl-1H-tetrazoles in synthesis and found that that potassio-and magnesiotetrazoles prepared in situ participate in carbonyl addition to 5-dibenzosuberenone (1) to yield the addition products, such as tertiary alcohol 146 ( Figure 13). 99 The Kobayashi group reported the synthesis of 5-benzothiophen-2-yl-5H-benzo[a,d]cyclohepten-5-ols 147 as substrates for the formation of a novel cage-like tetracyclic compound 148 via intramolecular [2+2]-photocyclization ( Figure 13); 100 compounds 147b and 148 were characterized by X-ray diffraction. 3-Lithioquinuclidin-2ene was generated as a novel nucleophilic intermediate for the synthesis of muscarinic agonists and antagonists, which were trapped with aldehydes and ketones (5 examples).…”
Section: Scheme 24 Synthesis Of L-cysteine Derivativesmentioning
confidence: 99%
“…The Wiedemann group reported some practical methods for the application of 5-metallo-1benzyl-1H-tetrazoles in synthesis and found that that potassio-and magnesiotetrazoles prepared in situ participate in carbonyl addition to 5-dibenzosuberenone (1) to yield the addition products, such as tertiary alcohol 146 ( Figure 13). 99 The Kobayashi group reported the synthesis of 5-benzothiophen-2-yl-5H-benzo[a,d]cyclohepten-5-ols 147 as substrates for the formation of a novel cage-like tetracyclic compound 148 via intramolecular [2+2]-photocyclization ( Figure 13); 100 compounds 147b and 148 were characterized by X-ray diffraction. 3-Lithioquinuclidin-2ene was generated as a novel nucleophilic intermediate for the synthesis of muscarinic agonists and antagonists, which were trapped with aldehydes and ketones (5 examples).…”
Section: Scheme 24 Synthesis Of L-cysteine Derivativesmentioning
confidence: 99%
“…Furthermore, one of the most important methods for synthesis of tetrazoles is the reaction of substituted amines with triethyl orthoformate and sodium azide [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Tetrazoles are a special class of five‐membered heterocyclic compounds with many C–N, N–N, and N=N bonds that possess excellent thermal stability, high density and enthalpy of formation, good chemical reactivity, which have attracted great interest as pharmaceuticals,13 photographic materials,4 polydentate linker,5,6 and energy materials 7. The halogenating reaction of tetrazoles is of utmost importance for increasing the activity and halogen compounds are promising chemical intermediates for synthesizing many excellent materials that are used in medicines, agricultural agents, and even energy materials 8,9…”
Section: Introductionmentioning
confidence: 99%
“…To date, the traditional methods for introducing halogen elements have included the following: (1) the [3+2] dipolar cycloaddition of dichloroisocyanide compounds with sodium azide1012 (Scheme ); (2) Sandmeyer reaction of amino tetrazole derivatives with sodium nitrite and cuprous halides13 (Scheme ); (3) direct halogenation of tetrazole derivatives by elemental halogen, NBS or NCS8,9,14 (Scheme ); (4) halogenating reaction of nitro compounds15,16 (Scheme ). However, the four approaches suffer from drawbacks such as high toxicity, high raw materials cost, a complex reaction procedure, harsh reaction conditions, and the formation of sensitive intermediates and by‐products that are difficult to separate.…”
Section: Introductionmentioning
confidence: 99%